Risk Management for “Stockists and Fabrication Abrasion Resistance Plate” in Indonesia - Ari Pranoto; Rhian Indradewa (Syntax Corporation Indonesia, 2023)
The abrasion-resistant steel supply and fabrication industry has many potential risks due to errors in the marketing process carried out by the company, lack of worker awareness and discipline regarding work instructions, lack of human resource management and company financial management. PT. Gipan Metal Teknik Indonesia has (PT. GMTI) problems in mitigating the risks it faces. This research aims to identify potential hazards and classify risk values at PT. GMTI. By determining the risk value, the company can provide risk control suggestions for each factor such as marketing, operations, human resources and finance. Key factors that influence the success of risk management implementation include management commitment, employee participation, effective communication, and access to necessary resources. In addition, this research also highlights the challenges faced by the fabrication industry in dealing with risks related to technological changes and increasingly stringent regulatory demands. The research results showed that there were 18 risk events and important implications for the abrasion-resistant steel supply and fabrication industry, emphasizing the importance of integrating risk management for each division at PT. GMTI.